Fundamental principles of law in the legal system of modern national and international law - Zadorozhna, Svitlana M; Kyryliuk, Nataliia V; Savchyn, Nelia M (Relações Internacionais no Mundo, 2021)
The fast development of international legal relations puts forward more and more requirements to legal regulation, which should be flexible and effective to achieve the goals of the modern international community. However, the current globalization processes in the international legal order have not only positive but negative consequences, which contributes to the necessity for the comprehensive analysis of the international legal system in the context of globalization. The study aims to examine the problem of defining the concept and nature of basic principles as the basis for the protection of human rights in the modern legal civilization space. In the study, the number of common law methods, general scientific and special scientific methods were used. The leading method of the study was a comparative legal method that allowed to compare principles of international law and other norms of international law, their place in the system of international law with the allocation of general and special interaction. As the result of the study, we characterized the main features of the basic principles as the basic rules of regulation of legal relations, analyzed the role of principles as fundamental principles of functioning of the international community, and substantiated the basic role of principles in the legal regulation of human rights. The study also determines the sources of the enshrinement of the basic principles of international law and its customary origin.
Keywords: globalization; fundamental norms of international law; human rights; international community; legal regulation